Peran Pemerintah dalam Tata Kelola Artificial Intelligence (AI) Berbasis Maqasid Al-Sharia - Andhika Yusuf; Muhammad Sunan; Ariel Nur Ramadhan; Kurniati Kurniati (Abdurrauf Science and Society, 2026)
The development of Artificial Intelligence (AI) has brought significant changes in various aspects of life, including the government, economy, education and public services sectors. However, the implementation of AI also raises various ethical, legal and social challenges that require proper regulation and supervision. This research aims to analyze the government's role in implementing Artificial Intelligence (AI) based on Maqasid al-Sharia, identify the opportunities and challenges faced by the government in its implementation, and examine the impact of the government's role on implementing AI that is in line with sharia values. This research uses a qualitative method with a library research approach sourced from scientific journals, books, policy documents and literature related to AI and Maqasid al-Sharia. The research results show that the government has a strategic role as a regulator, facilitator, supervisor, and policy director in ensuring the development and use of AI in accordance with the principles of protecting religion (hifz al-din), soul (hifz al-nafs), reason (hifz al-'aql), descendants (hifz al-nasl), and property (hifz al-mal). Opportunities for implementing AI based on Maqasid al-Sharia include increasing the efficiency of public services, strengthening government governance, and accelerating digital innovation that is oriented towards the benefit of society. Meanwhile, the challenges faced include regulatory limitations, human resource readiness, data security, and potential misuse of technology. An effective government role in implementing Maqasid al-Sharia-based AI can have a positive impact in the form of creating ethical, fair, transparent and sustainable use of technology oriented towards the welfare of society. [Perkembangan Artificial Intelligence (AI) telah membawa perubahan signifikan dalam berbagai aspek kehidupan, termasuk sektor pemerintahan, ekonomi, pendidikan, dan pelayanan publik. Namun, implementasi AI juga menimbulkan berbagai tantangan etika, hukum, dan sosial yang memerlukan regulasi serta pengawasan yang tepat. Penelitian bertujuan untuk menganalisis peran pemerintah dalam implementasi Artificial Intelligence (AI) berbasis Maqasid al-Sharia, mengidentifikasi peluang dan tantangan yang dihadapi pemerintah dalam penerapannya, serta mengkaji dampak peran pemerintah terhadap implementasi AI yang selaras dengan nilai-nilai syariah. Penelitian  menggunakan metode kualitatif dengan pendekatan studi pustaka (library research) yang bersumber dari jurnal ilmiah, buku, dokumen kebijakan, dan literatur terkait AI serta Maqasid al-Sharia. Hasil penelitian menunjukkan bahwa pemerintah memiliki peran strategis sebagai regulator, fasilitator, pengawas, dan pengarah kebijakan dalam memastikan pengembangan dan penggunaan AI sesuai dengan prinsip perlindungan agama (hifz al-din), jiwa (hifz al-nafs), akal (hifz al-'aql), keturunan (hifz al-nasl), dan harta (hifz al-mal). Peluang implementasi AI berbasis Maqasid al-Sharia meliputi peningkatan efisiensi pelayanan publik, penguatan tata kelola pemerintahan, serta percepatan inovasi digital yang berorientasi pada kemaslahatan masyarakat. Sementara itu, tantangan yang dihadapi mencakup keterbatasan regulasi, kesiapan sumber daya manusia, keamanan data, serta potensi penyalahgunaan teknologi. Peran pemerintah yang efektif dalam implementasi AI berbasis Maqasid al-Sharia dapat memberikan dampak positif berupa terciptanya pemanfaatan teknologi yang etis, adil, transparan, dan berorientasi pada kesejahteraan masyarakat secara berkelanjutan.]